TRANSITIONAL JUSTICE AND THE CRIMINAL RESPONSIBILITY OF JUDGES ([S.l.])
1 online resource
Keywords: This collective volume delves into the criminal responsibility of judges under authoritarian regimes, with case studies from Germany, Argentina, and Chile, examining their involvement in criminal human rights abuses and failures to protect victims from such crimes.Through comparative analysis, this volume offers insights into the legal and doctrinal challenges of prosecuting judicial involvement in crimes such as murder ('judicial murder'), kidnapping, unlawful detention, and torture. Bridging a gap in transitional justice and international criminal law literature, it focuses on the rarely explored criminal responsibility of judges beyond judicial misconduct. In doing so, it provides readers with a deeper understanding of judicial roles in authoritarian regimes and the complex legal standards involved in prosecuting such cases. It also informs the ongoing discourse on judicial accountability and the potential legal implications for judges in contemporary contexts.Transitional Justice and the Criminal Responsibility of Judges is ideal for students, scholars, and civil servants or practitioners working in the domestic or the international criminal justice system.